Understanding the scope of intracardiac echocardiography in catheter ablation of ventricular arrhythmia - Ma, Chuanzhen; Chen, Tongshuai; Chen, Yanbo; Ge, Junye; Han, Wenqiang; Wang, Qinhong; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2022)
Over the last few decades, catheter ablation has emerged as the first-line treatment for ventricular arrhythmias. However, detailed knowledge of cardiac anatomy during the surgery remains the prerequisite for successful ablation. Intracardiac echocardiography (ICE) is a unique imaging technique, which provides real-time visualization of cardiac structures, and is superior to other imaging modalities in terms of precise display of cardiac tissue characteristics as well as the orientation of anatomical landmarks. This article aimed to introduce the various advantages and limitations of ICE in the ablation of ventricular arrhythmias.